CONSTRAINTS PERCEIVED BY THE FARMERS IN ADOPTION OF VARIOUS DAIRY ANIMAL MANAGEMENT PRACTICES - MODI, R. J.; ISLAM, M. M.; PATEL, N. B.; PRAJAPATI, K. B.; WADHWANI, K. N. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTThe study was carried out in Sabarkantha district of Gujarat to identify the variousconstraints perceived by the farmers in adoption of dairy animal management practices. Arandom sample of 100 farmers were selected from 5 talukas of the district and theconstraints in adoption of management practices in aspect of housing, feeding, breeding,milking & health care management practices were studied. The result of study depicted thatlack of knowledge of cheap and scientific housing, lack of knowledge for efficient utilizationof feed and fodder, lack of knowledge for feeding mineral mixture, poor result of ArtificialInsemination, repeat breeding, lack of knowledge about scientific method of milking and lackof knowledge to control ectoparasite were constraints perceived by the farmers.Key words: Constraints, Adoption, Dairy Animal Management Practices.